A tissue‐specific screen of ceramide expression in aged mice identifies ceramide synthase‐1 and ceramide synthase‐5 as potential regulators of fiber size and strength in skeletal muscle. Issue 1 (6th November 2019) - Tosetti, Bettina; Brodesser, Susanne; Brunn, Anna; Deckert, Martina; Blüher, Matthias; Doehner, Wolfram; Anker, Stefan D.; Wenzel, Daniela; Fleischmann, Bernd; Pongratz, Carola; Peters, Franziska; Utermöhlen, Olaf; et al.
Abstract: Loss of skeletal muscle mass is one of the most widespread and deleterious processes in aging humans. However, the mechanistic metabolic principles remain poorly understood. In the framework of a multi‐organ investigation of age‐associated changes of ceramide species, a unique and distinctive change pattern of C16:0 and C18:0 ceramide species was detected in aged skeletal muscle. Consistently, the expression of CerS1 and CerS5 mRNA, encoding the ceramide synthases (CerS) with substrate preference for C16:0 and C18:0 acyl chains, respectively, was down‐regulated in skeletal muscle of aged mice. Similarly, an age‐dependent decline of both CerS1 and CerS5 mRNA expression was observed in skeletal muscle biopsies of humans. Moreover, CerS1 and CerS5 mRNA expression was also reduced in muscle biopsies from patients in advanced stage of chronic heart failure (CHF) suffering from muscle wasting and frailty. The possible impact of CerS1 and CerS 5 on muscle function was addressed by reversed genetic analysis using CerS1 Δ/Δ and CerS5 Δ/Δ knockout mice. Skeletal muscle from mice deficient of either CerS1 or CerS5 showed reduced caliber sizes of both slow (type 1) and fast (type 2) muscle fibers, fiber grouping, and fiber switch to type 1 fibers. Moreover, CerS1 ‐ and CerS5 ‐deficient mice exhibited reduced twitch and tetanus forces of musculus extensor digitorum longus . The findings of this study link CerS1 and CerS5 to histopathological changes and functional impairment of skeletal muscle in mice that might also play a functional role for the aging skeletal muscle and for age‐related muscle wasting disorders in humans. Abstract : In skeletal muscle of aged mice and humans, the expression of CerS1 and CerS5 and their corresponding reaction products, C16 and C18 ceramides, are reduced. Genetic ablation of CerS1 or CerS5 in mice led to smaller caliber sizes of type 1 and type 2 muscle fibers and reduction of muscle strength. Patients with chronic heart failure suffering from muscle weakness presented with decreased CerS1 and CerS5 expression, suggesting that CerS1 and CerS5 may also be linked to functional deficiencies of skeletal muscle in humans.